2020
DOI: 10.24843/soca.2020.v14.i01.p11
|View full text |Cite
|
Sign up to set email alerts
|

Bauran Pemasaran Olahan Lidah Buaya Terhadap Keputusan Pembelian Secara E-Commerce Ukm I Sun Vera

Abstract: The rapid growth in internet users in Indonesia makes the e-commerce business increasingly fierce by business people. UKM I Sun Vera is one of the UKM that develops e-commerce marketing business of processed aloe vera products, but in the implementation of UKM I Sun Vera still experience some obstacles such as sales promotions carried out less than the maximum, less skilled labor, limited knowledge of applications or online business systems so that consumer purchasing decisions in e-commerce are low on the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…A study by Mu'min, et al (2014) stated that there was a high enough and significant correlation between agricultural diversification and farmers' income in Belawang Village, Barito Kuala Regency. This was confirmed by the results of the study by Suryati, et al (2020) with research on the theme of e-commerce purchasing decisions. The results showed that there was an effect of product variations on consumer decisions to buy products in e-commerce.…”
Section: Profiles Of E-commerce User Sellers On Vegetable Marketingsupporting
confidence: 71%
See 1 more Smart Citation
“…A study by Mu'min, et al (2014) stated that there was a high enough and significant correlation between agricultural diversification and farmers' income in Belawang Village, Barito Kuala Regency. This was confirmed by the results of the study by Suryati, et al (2020) with research on the theme of e-commerce purchasing decisions. The results showed that there was an effect of product variations on consumer decisions to buy products in e-commerce.…”
Section: Profiles Of E-commerce User Sellers On Vegetable Marketingsupporting
confidence: 71%
“…The results showed that the type of ecommerce platform most used by greengrocers using e-commerce in Bali Province was Instagram. In line with a study by Suryati, et al (2020) which analyzed products in the agricultural sector, it is stated that the e-commerce platform to buy processed aloe vera products were dominant on Instagram. This is because the social media that is most often used in Indonesia is Instagram.…”
Section: Marketing Management Activities On Ecommerce Platformsmentioning
confidence: 66%